The Role of Business Analysts in Enhancing Customer Satisfaction through Advanced Business Systems - Tarun Teja Reddy Palyam (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Business Systems Analysts (BSAs) play a pivotal role in today’s digital-first business environment, particularly in sectors such as insurance, fraud detection, and e-commerce. This article examines the critical function of BSAs in leveraging advanced business systems to drive operational efficiency, risk mitigation, and customer satisfaction. With the global business intelligence market projected to reach 33.3 billion by 2025, the demand for skilled BSAs continues to grow. Their unique ability to bridge technical capabilities with business needs positions them as key enablers of digital transformation. Through case studies and industry data, this research illuminates how BSAs contribute to project success, cost reduction, and enhanced customer experiences. The article also explores emerging trends and technologies that are shaping the future of business systems analysis, highlighting the evolving nature of the BSA role in an increasingly data-driven business landscape. This revised abstract provides a more condensed overview of the article’s content, touching on the key points without duplicating the detailed information presented in the introduction. It also emphasizes the forward-looking aspects of the study and its relevance to current business trends.